Low Chlorine Residual and Intermittent Flow Lead to Coliforms Presence: A Study Case on Banda Aceh Water Supply System - Fathul Mahdariza (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Even though the water is supplied from Water Treatment Plant 24 hours a day, some consumers of Tirta Daroy Water Supply Company receive water in their taps intermittently. This condition leads to several reported pipe breaks and coliforms presence, as well. Tirta Daroy conducts a quality control activity so called Pamkor on regular basis. This study is conducted to analyse data obtained from this activity during 2014, with the focus on the total coliforms for total 161 sampling connections. The result demonstrates that the coliforms presence is encouraged by the low chlorine residual and intermittent supply. Additional finding shows these two conditions occur mainly at the areas which have long distance to the water treatment plant.